PENGARUH BRAND IMAGE AKTIVITAS DIGITAL MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN TOYOTA (STUDI KASUS PADA AUTO2000 DI MALANG RAYA) - Sutomo Gautama (Universitas PGRI Yogyakarta, 2026)
The purchase decision is a crucial stage in the marketing process because it is the main indicator of the success of a company's marketing strategy. Auto2000, where the dealership continues to influence Toyota vehicle purchase decisions amidst the increasingly competitive automotive market. In this context, the role of brand image, marketing strategy (including digital marketing), and service quality is crucial for winning the competition, as today's consumers are highly selective and increasingly rely on online information in the purchasing process. This study employed a quantitative approach with a causal-associative approach. The study population was spread across Greater Malang (Auto2000 Sutoyo, Auto2000 Sukun, and Auto2000 Singosari) with a total of 1,910 people. The sample size used the Slovin formula with a margin of error of 8%, amounting to 145 respondents. The sampling technique used was proportional stratified random sampling. Data analysis in this study was conducted through two main stages: descriptive analysis and inferential analysis (multiple linear regression) using SPSS version 25 software.The research results show that, partially and simultaneously, brand image, digital marketing, and service quality have a positive and significant influence on purchasing decisions. Service quality is the variable with the most dominant influence on purchasing decisions.